Can transcutaneous bilirubinometry reduce the need for blood tests in jaundiced full term babies?. Issue 3 (1st May 2002) - Briscoe, L; Clark, S; Yoxall, C W
Abstract : Background: Previous studies have suggested that transcutaneous bilirubinometry (TcB) may provide a useful method for screening for significant jaundice, thereby reducing unnecessary blood tests. These studies have not allowed an estimation of the magnitude of such a benefit. Objectives: To evaluate the accuracy of TcB as a method of determining the need for serum bilirubin (SBR) measurements in full term babies and to quantify the magnitude of any benefit. Subjects: Babies born at more than 34 weeks gestation who had not previously been exposed to phototherapy and were requiring blood sampling in the first week of life. Method: TcB measurements were made at the same time as blood sampling. SBR was measured in all blood samples. For jaundiced babies, the ability of TcB to detect significant jaundice (SBR > 249 μmol/l) was evaluated. Results: There was a correlation between SBR and TcB measurements (n = 303, r = 0.76, p < 0.0001), but the 95% prediction interval for SBR from TcB was wide (± 88.3 μmol/l). For the 285 jaundiced babies, the area under the receiver operator characteristic curve was 0.89. A TcB value of 18 detected significant jaundice with a sensitivity of 100% and a specificity (95% confidence interval) of 45% (39% to 51%). If blood samples had only been taken from babies with a TcB value greater than 18, the number of samples taken would have been reduced by 34%. Conclusions: SBR cannot be measured accurately by TcB. However, TcB measurements can be used to determine the need for blood sampling in jaundiced babies and will reduce the number of blood samples taken. Recent improvements in TcB may improve the performance of this method.